Pengembangan E-Modul Berbasis Problem Based Learning (PBL) untuk Memberdayakan Kemampuan Pemecahan Masalah Siswa - Putri, Feryda Indriyanti; Setiawati, Esti; Novianto, Victor; Lestari, Emi Tipuk (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study was to produce a PBL-based E-Module and to determine the validity, practicality, and effectiveness of the PBL-based E-Module in empowering students' problem-solving skills. This study used a research and development design and approach with the ADDIE model (analyze, design, development, implementation, and evaluation). Data collection methods used interviews, observation, questionnaires/surveys, documentation, and tests. Data analysis techniques focused on the validity, practicality, and effectiveness of the new product, using descriptive, evaluative, and experimental methods, with the main instruments being expert validation questionnaires (media, materials, practitioners) and user response questionnaires (students/test subjects) analyzed using a Likert scale and percentages to assess product feasibility, as well as qualitative data for improvement. The results showed that the PBL-based E-Module had been successfully developed. The PBL-based E-Module is valid and feasible to use with overall validation results from media experts in the “Very Good” qualification with an average score of 96% and “Feasible to use in the field without revision” while the overall validation results from material experts in the “Very Good” qualification with an overall average of 97.4% and “Feasible to use in the field without revision”. The PBL-based e-module is practical to use, with overall practicality test results from education practitioners qualifying as “Very Good” with an average score of 97.95% and “Suitable for field testing without revision.” Meanwhile, the practicality test results from a user group of 36 students obtained an average total score of 93.03% and were rated “Very Good” and “Suitable Without Revision”. The use of PBL-based E-Module teaching media is very effective in empowering students' problem-solving skills compared to the use of PowerPoint teaching media, based on the ANCOVA test results, which obtained a Sig. value of <0.001 (< 0.05). Keywords: PBL-based E-Module, Problem-Solving Skills